2004
DOI: 10.1097/00004770-200401000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Ca(OH)2 Associated with Different Vehicles: Chromatographic Study (High-performance Liquid Chromatography)

Abstract: Using high-performance liquid chromatography (HPLC), small amounts of liquid samples in which 25 premolar human teeth were immersed were evaluated. Each tooth was immersed separately in 800-ml flasks with distilled ultra-pure deionized water and remained there for 1678 h after the filling of their canals with Ca(OH)2 associated with different vehicles: group 1: polyethylene glycol and colophon (Calen); group 2: glycerin and camphorated paramonochlorophenol; group 3: camphorated paramonochlorophenol; group 4: g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…PEG 400 is a suitable solvent for calcium hydroxide, and gives superior ion release into roots than a water solvent [ 31 , 39 , 40 ]. This can be attributed to the large number of ethylene oxide groups along its backbone, which allows PEG to form complexes with calcium ions, driving the dissociation of calcium hydroxide, and thus releasing more free hydroxyl ions [ 31 ].…”
Section: Solvents and Their Effects On Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…PEG 400 is a suitable solvent for calcium hydroxide, and gives superior ion release into roots than a water solvent [ 31 , 39 , 40 ]. This can be attributed to the large number of ethylene oxide groups along its backbone, which allows PEG to form complexes with calcium ions, driving the dissociation of calcium hydroxide, and thus releasing more free hydroxyl ions [ 31 ].…”
Section: Solvents and Their Effects On Solubilitymentioning
confidence: 99%
“…After placement of a calcium hydroxide medicament paste into the root canal, the process of hydroxyl ion diffusion will begin, being more rapid in the cervical third of the root than in the apical third where the tubules are smaller and less numerous. The effects of the released hydroxyl ions can be seen on the inner root dentine (i.e., adjacent to the root canal) within a matter of hours, and the middle regions of the dentine over the following week, taking 2–3 weeks to reach peak pH levels [ 7 , 31 , 39 , 40 , 41 ].…”
Section: Solvents and Their Effects On Solubilitymentioning
confidence: 99%
“…Calcium hydroxide [Ca(OH) 2 ] is one of the more popular medicaments used for this purpose. It is known that after instrumentation, irrigation and a Ca(OH) 2 dressing, more canals are free of bacterial growth than those devoid of a dressing (4 -6), and a recent review of the literature has confirmed its antimicrobial effectiveness (7) and good diffusion through dentin (8). One reason for the efficacy of Ca(OH) 2 is considered to be the alkaline environment created by its application that discourages bacterial growth.…”
mentioning
confidence: 99%
“…Many theories have been proposed as the causative factors for the lack of achievement of successful anesthesia in mandibular teeth with irreversible pulpitis. The hyperalgesia triggered by the inflammatory process leading to alteration of neural response [4], raised levels of prostaglandins and activation of nociceptors [1], lowered pH which hampers the ability of the anesthetic to penetrate the membrane [1, 5], tetrodotoxin resistant sodium channels shown in human symptomatic dental pulp and trigeminal ganglion [6], the sprouting of the nerve fibers [7], and increase in neuropeptides such as Substance P and calcitonin gene-related peptide (CGRP) resulting in the expression of inflammatory mediators [8] are some suggestions made to explain the reason of anesthetic failure associated with acute symptomatic teeth. Nonmyelinated C-fibers which pose difficulty in terms of provision of anesthesia have also been proposed as a contributing factor [9].…”
Section: Introductionmentioning
confidence: 99%